Rancangan Model Artificial Neural Network untuk Memprediksikan Penyakit Jantung Koroner di RSUD Zainoel Abidin Banda Aceh - M. Rizki Fazrian Danu; Purwadhi; Ignatius Wiseto Prasetyo Agung (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to develop and evaluate an Artificial Neural Network (ANN) model in predicting the risk of coronary heart disease (CHD). This research uses a quantitative approach with research and development methods to develop and evaluate the integration of the ANN model in predicting CHD. This research uses a research and development research design which involves several main stages, namely literature study, data collection, data preprocessing, ANN model building, model training and testing, and results analysis. From the research results, it can be concluded that hospitals can implement an ANN-based model as a hospital management system that can carry out early detection of coronary heart disease. Implementing the ANN model into a hospital application or website will increase operational efficiency. Thus, the ANN model implemented into applications or websites for hospital management systems will support digital transformation in the health sector and provide more effective services to those who use hospital services.